Analisis Postur Kerja Menggunakan Metode Ovako Work Analysis System (OWAS) pada UKM Pengolahan Ikan - Khairul Hadi; Iing Pamungkas; Risnadi Irawan; Abdiel Khaleil Akmal; Heri Tri Irawan; Adib Adib (Jurnal Optimalisasi, 2021)
UKM Stefen Aluy is one of the businesses engaged in processing fresh fish into salted fish. When conducting preliminary research in the field, several causes of Musculoskeletal Disorder (MSDs) complaints were found. The results of the preliminary study, 66.7% of workers complained of pain in the waist, 50% of workers complained of back and waist pain, 33.3% of workers complained of pain in the left and right elbows and 16.7% of workers complained of pain in the thighs. Cumulatively from the preliminary research conducted, the parameters of the level of pain complaints were 21.4%, moderate pain, 33.3% and 45.2% pain. If this condition is ignored continuously for a long time, it has the potential to cause injury or low back pain to workers. To identify and analyze work attitudes, the Ovako Work Analysis System (OWAS) method is used, which is a method to identify and analyze work attitudes. The results of the study concluded that based on biomechanical measurements of work postures, there were several work postures that were included in 3 (three) assessment categories, namely the work posture of moving fish at the sorting station, working posture of moving fish at the weeding station, and working posture of moving fish at the packaging station.